Penerapan Layanan Bimbingan Kelompok dengan Teknik Visualisasi Terarah untuk Mengurangi Kecemasan Berlebihan - Zahra, Alvina; Wastuti, Sri Ngayomi Yudha; Salamah, Ummi (Algebra : Jurnal Pendidikan, Sosial dan Sains, 2025)
This study aims to implement group guidance services with guided imagery techniques as an effort to reduce excessive anxiety in class XI F2 students at SMA Negeri 10 Medan. Anxiety is a common problem that can affect students' physical and psychological health, so it needs to be handled effectively. The research method used is Guidance and Counseling Action Research (PTBK) with two cycles, each consisting of planning, action, observation, and reflection. The subjects of the study were 5 students who were identified as experiencing excessive anxiety based on the assessment results. The results showed that the application of guided imagery techniques was effective in increasing students' sense of calm and confidence. Evaluation of both cycles showed significant improvements in students' affective, cognitive, and psychomotor aspects, as well as a positive impact on their involvement in the guidance process. This study is expected to contribute to the development of guidance and counseling practices in schools and enrich knowledge about anxiety management techniques.